Expanding our classrooms: metaphors, dissidence and migrants (Praxis Educativa, 2026)
This article proposes an explanation for the relevance of designing expanded classrooms based on the arts. To this end, it draws on authors who occupy a central position in the field of education (Dewey, Greene, Camilloni, Litwin, Augustowsky, among others) and illustrates its point with a corpus of experiences involving teachers, students, and graduates of Literature and Arts. Throughout the article, it incorporates fragments of literary texts, culminating in a meta-analytical reflection on the practice of teaching, nature, and writing.
Keywords: narrative research; education; expanded classrooms; artistic; practices